ANALISIS PENANAMAN NILAI-NILAI PANCASILA DALAM PEMBELAJARAN PKN PADA SISWA KELAS III SD NEGERI LAMPER KIDUL 01 - Rizky Safitri, Rafika; Kiswoyo , Kiswoyo; Arisyanto, Prasena (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the importance of instilling Pancasila values in Civic Education (PKn) learning as an effort to build character among elementary school students. The study aimed to analyze the implementation of Pancasila values in Civic Education learning for third-grade students at SD Negeri Lamper Kidul 01. This study employed a qualitative approach with a descriptive research design. The research subjects consisted of one third-grade teacher and 26 third-grade students. Data were collected through observation, interviews, questionnaires, and documentation. Data analysis used the Miles, Huberman, and Saldaña model, including data reduction, data display, and conclusion drawing. The findings revealed that the implementation of Pancasila values was carried out through lesson planning, learning implementation, and character habituation activities. Teachers integrated Pancasila values through lecture, question-and-answer, and role-playing methods. Role-playing was found to be an effective strategy in helping students internalize Pancasila values because it increased students’ active participation in the learning process. The internalization of values was reflected in students’ attitudes such as cooperation, discipline, responsibility, helping others, and respecting others’ opinions. The main obstacle in instilling Pancasila values originated from the family environment, which had not fully provided optimal character habituation for studentsKeywords: Pancasila values, Civic Education, character education